2016
DOI: 10.1016/j.cpr.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and the psychosis spectrum: A review of symptom specificity and explanatory mechanisms

Abstract: Traumatic life events have been robustly associated with various psychosis outcomes, including increased risk of psychotic disorders, the prodrome of psychosis, and dimensional measures of psychotic symptoms, such as attenuated positive psychotic symptoms. However, trauma exposure has been linked to various mental disorders; therefore, the specificity of trauma exposure to psychosis remains unclear. This review focuses on two understudied areas of the trauma and psychosis literature: 1) the specificity between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
136
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(161 citation statements)
references
References 183 publications
14
136
1
8
Order By: Relevance
“…Current literature and reviews (Fusar‐Poli et al, ; Gibson, Alloy, & Ellman, ) have shown trauma to be an important risk factor among those at high risk of psychosis. Interestingly, although our sample all met criteria for being at CHR, we found a further distinction between those with and without a family history.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature and reviews (Fusar‐Poli et al, ; Gibson, Alloy, & Ellman, ) have shown trauma to be an important risk factor among those at high risk of psychosis. Interestingly, although our sample all met criteria for being at CHR, we found a further distinction between those with and without a family history.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood adversity is also a risk factor for bipolar I disorder 167 . Childhood adversity is clearly linked to reality distortion symptoms, while its association with negative symptoms is less consistent and understudied, and data on disorganization are lacking 168 . With regard to traits, childhood adversity is consistently associated with psychoticism, and preliminary evidence supports a link to detachment 169,170 .…”
Section: Validity Evidencementioning
confidence: 99%
“…Além disso, ambos têm no ambiente um elemento comum: na esquizofrenia, fatores do ambiente (interno e externo) provocam um efeito patogênico sobre o sistema nervoso do paciente afetado; nas desordens dissociativas, uma das características essenciais é a interrupção das funções que integram a percepção do ambiente. O trauma, ocorrido na primeira infância, é um dos fatores ambientais de risco para esquizofrenia e condição para início de experiências dissociativas, como o TDI (Gibson, Alloy, & Ellman, 2016;Negro Júnior, Negro, & Louzã, 1999;Van der Hart, 2012). Esses fatores integram o foco deste trabalho.…”
unclassified
“…Na primeira, citam-se como fatores traumáticos a negligência emocional, o abandono, o desamparo e a rejeição na infância, associados ao surgimento de sintomas psicóticos ou repercussões nocivas na fase adulta. A extensão dos danos decorrentes desses fatores varia de acordo com a vulnerabilidade de cada paciente, uma vez que os traumas podem se referir a um único acontecimento externo, como abuso sexual ou estupro ou a um acúmulo deles (Gibson, Alloy, & Ellman, 2016;Kumar, Castellani, Maiti, O'reilly, & Singh, 2013).…”
unclassified
See 1 more Smart Citation